2022
DOI: 10.1177/23197145221112743
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Willingness to Pay for Agri-Food Products Delivered with Electric Vehicles in the Short Supply Chains

Abstract: This study aims at investigating the consumers’ willingness to pay (WTP) for agri-food products delivered in the farmers markets with electric vehicles (EVs). The empirical analysis has been carried out by administering an online questionnaire to 273 consumers within a hypothetical context. A multiple price list has been provided in order to measure the price premium for 1 kg of oranges transported by EVs comparing with the ones transported by traditional vehicles. A Tobit regression model has been used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 97 publications
2
12
0
Order By: Relevance
“…According to the analysis of the model results in Figure 2 , it is clear that soil information transparency has a significant positive effect on competence trust ( β = 0.230, p < 0.05), and H1a is supported. This result is consistent with previous studies such as Chen (2007) , Laureti and Benedetti (2018) , and Mezger et al (2020) , in which consumers pay attention to the environmental and sustainability of the production process of agricultural products in terms of their impact on human health when making green produce purchases ( Galati et al, 2022 ), the active disclosure of soil information transparency of green agricultural products by online sellers promotes consumers’ perception of the competence of that online seller’s operational skills and expertise. However, the effect of soil information transparency on benevolence trust is negatively insignificant ( β = −0.138, p > 0.05), which is not consistent with the initial H1b .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the analysis of the model results in Figure 2 , it is clear that soil information transparency has a significant positive effect on competence trust ( β = 0.230, p < 0.05), and H1a is supported. This result is consistent with previous studies such as Chen (2007) , Laureti and Benedetti (2018) , and Mezger et al (2020) , in which consumers pay attention to the environmental and sustainability of the production process of agricultural products in terms of their impact on human health when making green produce purchases ( Galati et al, 2022 ), the active disclosure of soil information transparency of green agricultural products by online sellers promotes consumers’ perception of the competence of that online seller’s operational skills and expertise. However, the effect of soil information transparency on benevolence trust is negatively insignificant ( β = −0.138, p > 0.05), which is not consistent with the initial H1b .…”
Section: Discussionsupporting
confidence: 91%
“…The online seller provides timely information about the quality of irrigation water used in the production of green agricultural products products in terms of their impact on human health when making green produce purchases (Galati et al, 2022), the active disclosure of soil information transparency of green agricultural products by online sellers promotes consumers' perception of the competence of that online seller's operational skills and expertise. However, the effect of soil information transparency on benevolence trust is negatively insignificant (β = −0.138, p > 0.05), which is not consistent with the initial H1b.…”
Section: Water Information Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…The motivations for organic food consumption have been extensively explored in previous literature. Studies have found that consumers' motivations for purchasing organic food include economic reasons (e.g., price), social/cultural reasons (e.g., social status), personal reasons (e.g., egoistic and altruistic values), and product reasons (e.g., attributes such as health and safety; Dorce et al, 2021;Galati et al, 2022;Knaggs et al, 2022;Wei et al, 2022). In particular, concern for health, environmental protection, food safety, and taste have been identified as the main purchase motivations for organic food (Hemmerling et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The other is based on consumers' psychological decision-making process. The influence of credence attributes on consumers' purchase attitudes and intentions was analyzed, and it was found that credence attributes such as health, safety, and environment-related factors of organic food all lead to positive attitudes and purchase intentions (Szolnoki and Hauck, 2020;Galati et al, 2022). These studies on credence attributes have provided insights into consumers' motivations for purchasing organic food.…”
Section: Introductionmentioning
confidence: 99%